Analisis Yuridis terhadap E – Purchasing dalam Pengadaan Barang/Jasa Pemerintah - Iwan Kurniawan (Universitas Internasional Batam, 2019)
Procurement of Government Goods & Services is an activity in order to obtain goods and services by Ministries, Institutions, Regional Work Units, other Institutions. Procurement of government goods / services electronically can be done through e-tendering or e-purchasing. With the procurement of goods and services, the government opens opportunities as well as challenges for Indonesian entrepreneurs, including Micro, Small and Medium Enterprises. The government should take an important role in supporting Micro, Small and Medium Enterprises with efforts to foster a conducive business climate for businesses and support the development of Micro, Small and Medium Enterprises.